STRATEGI PEMASARAN POTENSI WISATA ALAM GUA KISKENDO KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - , FAKHRYZA ASYHAR H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kiskendo Cave is one of the natural attractions that exist in Kulon Progo, Daerah Istimewa Yogyakarta. Kiskendo Cave is very potential to be a tourist area especially nature Tourism, becauseto natural beauty that is in Kiskendo Cave and surrounding areas. Although Kiskendo Cave has Tourism potential that very much but can not develop without the support of the relevans stakeholder oasis in the Development and marketing of Tourism potential this. In addition to the Development to be done, the manager of Kiskendo cave must conduct a marketing strategy to attract tourists to visi. The small number of caves in the area of Kulon Progo, may be one of special interest Tourism for the prospective tourists especially tourists of special interest tourists